STUDI EMPIRIS PENGARUH LIKUIDITAS, SOLVABILITAS DAN RASIO AKTIVITAS TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA PERIODE 2020-2022 - Hidayah, Fitriani Nur; Sumiyarsih, Sumiyarsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The purpose of this research is to examine and evaluate how liquidity, solvency, and activity ratios affect the profitability of manufacturing companies that are listed on the IDX between 2020 and 2022. Manufacturing firms that are listed on the Indonesia Stock Exchange for the 2020–2022 timeframe make up the study's population. Purposive sampling was used to choose the study's sample, which consisted of 54 manufacturing enterprises that fit the requirements and were listed on the IDX between 2020 and 2022. In this study, the SPSS application is used as a test tool for the multiple regression analysis method of hypothesis testing. According to the study's findings, activity and liquidity significantly boost profitability. while solvability has a negative insignificant effect on profitability and simultaneously liquidity, solvability and activity have a positive and significant effect on the profitability of manufacturing companies listed on the IDX in the period 2020 - 2022.